Advances in computers., volume 66, Quality software development - Zelkowitz, Marvin V., 1945- (Amsterdam ; Boston : Elsevier Academic Press, 2006)
This volume of Advances in Computers is number 66 in the series that began back in 1960. This series presents the ever changing landscape in the continuing evolution of the development of the computer and the field of information processing. Each year three volumes are produced presenting approximately 20 chapters that describe the latest technology in the use of computers today. Volume 66, subtitled "Quality software development," is concerned about the current need to create quality software. It describes the current emphasis in techniques for creating such software and in methods to demonstrate that the software indeed meets the expectations of the designers and purchasers of that software. Key features: - In-depth surveys and tutorials on software development approaches. - Well-known authors and researchers in the field. - Extensive bibliographies with most chapters. - All chapters focus on software development issues. - Discussion of high end computing applications, a topic generally not understood by most software professionals. - In-depth surveys and tutorials on software development approaches. - Well-known authors and researchers in the field. - Extensive bibliographies with most chapters. - All chapters focus on software development issues. - Discussion of high end computing applications, a topic generally not understood by most software professionals.
Calculating software process improvement's return on investment / Rini van Solingen and David F. Rico -- Quality problem in software measurement data / Pierre Rebours and Taghi M. Khoshgoftaar -- Requirements management for dependable software systems / William G. Bail -- Mechanics of managing software risk / William G. Bail -- The PERFECT approach to experience-based process evolution / Brian A. Nejmeh and William E. Riddle -- The opportunities, challenges, and risks of high performance computing in computational science and engineering / Douglass E. Post, Richard P. Kendall and Robert F. Lucas.
Includes bibliographical references and indexes.
Keywords: Computer software -- Development; Electronic books